ANALISIS DETERMINAN TINGKAT KEMISKINAN DI INDONESIA - MARISA MARISA (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This research was purpose to analyze the effect of economic growth, government expenditure, inflation, andunemployment on the level of poverty in Indonesia. This study uses time series data in the form of annual data from 1997-2017 period. The analysis technique in this study uses cointegration approach and Error Correction Model (ECM) and multiple linear regression models. The estimation results show that the variable of economic growth are statistically significant and have a negative effect on the level of poverty in Indonesia. While the variable of government expenditure, inflation and unemployment are not statistically significant in influencing the level of poverty in Indonesia.The results of this study imply that economic growth is a macroeconomic variable that plays a major role in reducing the level of poverty in Indonesia.Keywords: Economic Growth; Government Expenditure; Inflation; Unemployment; Poverty